Synthesis of Chiral Fluorides by Sequential Organocatalyzed Desymmetrization of Glutaric Anhydrides and Photoredox-Catalyzed Decarboxylic Fluorination - Zhao, Jia-Jia; Yu, Shouyun (Synlett, 2020)
We have developed an efficient method for the preparation of chiral fluorinated compounds by sequential organocatalyzed desymmetrization of 3-substituted glutaric anhydrides and photoredox-catalyzed decarboxylic fluorination. Chiral fluorides can be prepared in yields of up to 58% and with excellent enantioselectivities of up to 98% ee.
Keywords: sequential catalysis; organocatalysis; photoredox catalysis; fluoro compounds; asymmetric catalysis; desymmetrization